2021
DOI: 10.1093/milmed/usaa495
|View full text |Cite
|
Sign up to set email alerts
|

Firearm Suicide Among Veterans of the U.S. Military: A Systematic Review

Abstract: Introduction In the United States, firearm suicide represents a major cause of preventable, premature death among veterans. The purpose of this systematic review was to characterize the body of literature on veteran firearm suicide and identify areas for future research, which may facilitate the development of firearm suicide interventions in Veterans Health Administration (VHA) and non–Veterans Health Administration clinical settings. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Among a large cohort of veteran suicide decedents, 45 % had no mental health or substance use diagnosis, and those without such diagnosis were significantly more likely to die by firearm suicide than by other means [58]. Efforts to raise awareness of risk, discuss the importance of suicide risk assessment regardless of the presence of a diagnosis, create guidance for acceptable counseling on reducing access to firearms for those at risk of self-harm, and increase access to mental health services are underway at the VA [59], and additional work is needed to address firearm suicide specifically among veterans [60].…”
Section: Risk Factors For Firearm Suicidementioning
confidence: 99%
“…Among a large cohort of veteran suicide decedents, 45 % had no mental health or substance use diagnosis, and those without such diagnosis were significantly more likely to die by firearm suicide than by other means [58]. Efforts to raise awareness of risk, discuss the importance of suicide risk assessment regardless of the presence of a diagnosis, create guidance for acceptable counseling on reducing access to firearms for those at risk of self-harm, and increase access to mental health services are underway at the VA [59], and additional work is needed to address firearm suicide specifically among veterans [60].…”
Section: Risk Factors For Firearm Suicidementioning
confidence: 99%
“…Honor not only influences firearm ownership at both the state and individual levels (Bock et al, 2021;Brown, Imura, & Osterman, 2014;Cohen & Nisbett, 1994) but also influences limitations placed on firearm laws and regulations (Cohen, 1998). Given previous research showing that firearm ownership and firearm suicide rates are higher among veterans (Cleveland et al, 2017;Hoffmire & Bossarte, 2014;Theis et al, 2021) and that veterans tend to live in states with fewer firearm laws (Anestis & Capron, 2016), the present research provides a cultural lens through which to view veteran suicide by showing how honor cultures may make suicide among this already-at-risk group even more likely.…”
Section: Discussionmentioning
confidence: 81%
“…Second, although prior research on veteran suicide has observed regional differences in suicide rates (Hoffmire & Bossarte, 2014; Theis et al, 2021), not all southern and western states are classified as honor states (Cohen, 1998). Thus, the present work adds to the literature by demonstrating how the culture of honor framework can play a role in explaining public health outcomes, such as veteran suicide, and implicates the role of firearm accessibility in veteran suicide rates as well.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, a recent systematic review in the US highlighted that US veterans are at a substantially increased risk of firearm suicide and have higher rates of firearm ownership than the US general population. 43…”
Section: Introductionmentioning
confidence: 99%